Goethe's Faust: theatre of modernity - Schulte, Hans; Noyes, John K.; Kleber, Pia (Cambridge University Press, 2011)
"Faust has been called the fundamental icon of Western culture, and Goethe's inexhaustible poetic drama is the centrepiece of its tradition in literature, music and art. In recent years, this play has experienced something of a renaissance, with a surge of studies, theatre productions, press coverage and public discussions. Reflecting this renewed interest, leading Goethe scholars in this volume explore the play's striking modernity within its theatrical framework. The chapters present new aspects such as the virtuality of Faust, the music drama, the modernization of evil, Faust's blindness, the gay Mephistopheles, classic beauty and horror as phantasmagoria, and Goethe's anticipation of modern science, economics and ecology. The book contains an illustrated section on Faust in modern performance, with contributions by renowned directors, critics and dramaturges, and a major interview with Peter Stein, director of the uncut 'millennium production' of Expo 2000"--